The Gestating and Lactating Sow 2015
DOI: 10.3920/978-90-8686-803-2_14
|View full text |Cite
|
Sign up to set email alerts
|

14. Mammary blood flow and nutrient uptake

Abstract: Sow milk is the major source of nutrients for suckling piglets and taking into account the large litter sizes of our current sow genotypes, it is imperative to maximize nutrient use by the mammary gland. The amount of nutrients available to mammary tissue is dependent upon the concentrations of nutrients in blood and the rate of its flow to the lactating glands. Nutrient availability to the udder may be estimated by measuring mammary arteriovenous differences, and mammary blood flow can be measured either dire… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 52 publications
0
3
0
Order By: Relevance
“… Le Cozler et al (1999) observed sow arterial glucose concentration remained constant as time since birth of first piglet increased, and rapidly increased after the birth of the last pig until time of placenta expulsion. This may be due an increased demand of glucose as a precursor for lactose in milk synthesis once parturition is complete ( Farmer et al, 2015 ), or circulating hormones during parturition altering glucose regulation. Feyera et al (2018) demonstrated glucose and triglyceride extraction by the uterus increased 1.4- and 6-fold, respectively, during parturition compared with after parturition.…”
Section: Discussionmentioning
confidence: 99%
“… Le Cozler et al (1999) observed sow arterial glucose concentration remained constant as time since birth of first piglet increased, and rapidly increased after the birth of the last pig until time of placenta expulsion. This may be due an increased demand of glucose as a precursor for lactose in milk synthesis once parturition is complete ( Farmer et al, 2015 ), or circulating hormones during parturition altering glucose regulation. Feyera et al (2018) demonstrated glucose and triglyceride extraction by the uterus increased 1.4- and 6-fold, respectively, during parturition compared with after parturition.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, we saw no correlation between the LPS concentration in v. epigastrica and redness, warmth, hardness, and edema in the first 6 anterior glands. Moreover, no differences in LPS concentrations were detected between sows with and without PDS, indicating that increased inflammation was not induced by translocation of LPS from the udder to the bloodstream ( Farmer et al, 2015 ). These results are in line with previous studies indicating that predisposing factors other than bacterial infections must be present for PDS to develop ( Magnusson et al, 2001 ; Osterlundh et al, 2002 ; Gerjets et al, 2011 ; Kaiser et al 2018b ).…”
Section: Discussionmentioning
confidence: 99%
“…Milk precursors are digested in the gut, transported through the blood circulatory system, and finally absorbed by the MG. Nutrients accessible to the MG from the blood can interfere with the rate of MBF, which causes nutritional perturbation of MBF . A previous study suggested that insufficient availability of glucose decreased mammary plasma flow and decreased glucose uptake of the MG by 30% .…”
Section: Regulation Of Blood Flow In the Mammary Glandmentioning
confidence: 99%